Zum Problem der Stabilität der Klimabedingungen in Westsibirien während der Glaziale und Interglaziale - Weischet, W. (E&G Quaternary Science Journal, 1960)
The depression values of the summer temperature and also of the mean annual temperature in Western Siberia during the last glaciation, have been deduced. This calculation has been based on the different position of the boreal boundaries of the tundra and the continental deciduous forests during the ice ages and at the present time. According to these calculations the following depressions of summer temperature have been obtained: 5-8° C near the arctic circle and 2-4° C in the latitude of 50° North, in comparison with the 10-12° C depression in Central Europe. Afterwards it has been discussed whether or not these relatively small depressions can be explained exclusively on the basis of the higher continentality of the central part of Eurasia in comparison with the western or eastern part of this continent. As this seems to be impossible, it is necessary to look for other facts that could be related to this problem. In the opinion of the author the relative stability of climatic conditions in Western Siberia during the whole Quaternary could be easily explained by the change between the meridional-circulation (low-index-type), prevailing during the glacial periods, and the reinforced zonal-circulation (high-index-type) during the interglacial and postglacial periods.